Management of Tuberculosis: Are the Practices Homogeneous in High-Income Countries? - Méchaï, Frédéric; Cordel, Hugues; Guglielmetti, Lorenzo; Aubry, Alexandra; Jankovic, Mateja; Viveiros, Miguel; Santin, Miguel; Goletti, Delia; Cambau, Emmanuelle (Frontiers in Public Health, 2020)
Objectives: to evaluate and compare practices regarding the diagnosis, isolation measures and treatment of tuberculosis (TB) in high-income countries and mainly in Europe. Materials and methods: A survey was conducted from November 2018 to April 2019 within the ESCMID study group for mycobacterial infections (ESGMYC). The practices observed were compared to the main international guidelines. Results: Among 136 ESGMYC members, 64 (17 countries) responded to the questionnaire. In their practice, two (20.7%) or three sputum samples (79.3%) were collected for the diagno-sis of pulmonary TB, alternatively induced sputum (n = 37, 67.2%), bronchoscopy (34, 58.6%) and gastric aspirates (15, 25.9%). Nucleic acid amplification tests were performed by 41 (64%) respondents whatever the smear result, and by 47 (73%) in case of smear-positive specimens. NAAT and adenosine deaminase measurement were used for extrapulmonary TB diagnosis in 83.6% and 40.4% of cases, respectively. For isolation duration, 21 respondents (42.9%) are keeping isolation until smear negativity. An initial treatment without ethambutol was offered by 14% (n=9) of respondents. Corticosteroid therapy, cerebrospinal fluid open-ing pressure testing, and repeated lumbar puncture were carried out for central nervous system TB by 79.6%, 51.9% and 46.3% of the respondents, respectively. For patients with HIV-TB coinfection, the preferred antiretroviral therapy included dolutegravir 50mg BID (56.8%). Comparing with the recommendations of the main guidelines, the practices are not totally consistent. Conclusion: This study shows heterogeneous practices, particularly for diagnosis and isolation although rapid molecular testing is implemented in most centers. More standardization might be needed.